Application of the Crashing Method in the Construction of District Office Buildings Karangrejo - Mustofa, Imam (CIVED, 2023)
In the world of construction in the development sector, arrangements regarding cost, quality, and completion time of construction work are bound in the work contract and are decided before the construction work is carried out. This study aims to find out the total time and costs after adding working hours and knowing the comparison of time and costs from the initial plan with what has been done with additional working hours. Planning and control is something that cannot be explained in carrying out a project, this implementation requires a long time and serious effort and it depends on effective control. This research will speed up the schedule for the construction of the Karangrejo District Office Building project using the crashing method. From the results of the analysis and calculations described above, it can be concluded that the construction project for the Karangrejo District Office Building's total costs and project time under normal conditions is IDR 2,572,500,000 with a normal duration of 189 days. After adding 3 hours of overtime work, a total cost of Rp. 2,817,500,000 was obtained by consuming an accelerated duration of 180 days. In terms of project costs, applying acceleration by adding a 3-hour overtime system has increased costs by IDR 25,000,000 or more expensive than the normal project costs. Meanwhile, the duration experienced an increase of 4.70% or 9 days faster than the initial normal project duration.